Analisis Lingkungan Kerja dan Budaya Organisasi terhadap Kepuasan Kerja di Industri Tas dan Koper (INTAKO) Tanggulangin Sidoarjo - Arda Widanegara; Gendut Sukarno (Universitas Batanghari Jambi, 2022)
Currently, with the development of the era, the company's competition is also getting higher. In a company, there must be roles for employees and workers called Human Resources (HR). This study aims to determine the effect of the work environment and organizational culture on employee job satisfaction at INTAKO Tanggulangin Sidoarjo. Furthermore, the researchers used quantitative research as a type of this research in which the questionnaire was used as a means of measuring the answers of the respondents. In this study the population is all workers in INTAKO Tanggulangin Sidoarjo totaling 67 employees. In this study, the sampling technique used a saturated sample because the population was less than 100 so that the entire population in this study was used as a sample, amounting to 67 people. After being answered by the respondent, the answer will be analyzed using Smart PLS (Partial Least Square) to test the level of validity and reliability of an indicator and research variable which is included in the outer and inner models. The results of this study conclude that the work environment have positive effect but not significant and organizational culture have a significant positive effect on job satisfaction.